1988
DOI: 10.1113/expphysiol.1988.sp003210
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Electrolytes in the Rabbit Following Chronic Dietary Potassium Depletion

Abstract: SUMMARYTissue electrolytes were estimated in rabbits following chronic dietary K+ depletion, and after a week of subsequent K+ repletion. The heart, liver and brain all exhibited protection against K+ loss following K+ depletion, whereas skeletal muscle did not. Both Na+ and total magnesium were elevated in quadriceps, but not in other tissues. After

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

1989
1989
1990
1990

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
(7 reference statements)
0
5
1
Order By: Relevance
“…These observations are consistent with functional studies on rat myocytes (Fry et al 1984). Using a water content of 76% (von Zglinicki & Bimmler, 1986) (Ward, 1988). The results presented here show a somewhat higher [Na+]i than that reported for whole tissue 20 mm [Na+] but this value reflects an upward bias due to some cells with very high Na+.…”
Section: Pcontrasting
confidence: 54%
“…These observations are consistent with functional studies on rat myocytes (Fry et al 1984). Using a water content of 76% (von Zglinicki & Bimmler, 1986) (Ward, 1988). The results presented here show a somewhat higher [Na+]i than that reported for whole tissue 20 mm [Na+] but this value reflects an upward bias due to some cells with very high Na+.…”
Section: Pcontrasting
confidence: 54%
“…However, direct comparison with other techniques is difficult, as values are expressed in terms of mass of the area analysed. Previous studies (for example, Ward, 1988) have shown that total cardiac muscle electrolytes are unchanged following K depletion, and although the present results for Na, Mg and, in the mitochondria, K are consistent with this, there was a significant reduction in myofibrillar K. This relatively small (15 %) fall may well be masked in analyses of whole tissue by a lack of change in other regions of the cell (e.g. mitochondria), but it suggests that any adaptation to K depletion is not as effective as previously thought.…”
Section: Discussionmentioning
confidence: 98%
“…Male New Zealand White rabbits, with an average weight of 2-3 kg, were fed either a control or a K-deficient diet (< 0 1 mmol K/100 g; SDS Ltd) for 25 days as previously described (Ward, 1988(Ward, , 1990. The animals were anaesthetized with pentobarbitone (50 mg/kg) and the heart removed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations